Molecular Evolution of Apolipoprotein Multigene Family and the Original Functional Properties of Serum Apolipoprotein (LAL2) in Lampetra japonica - Han, Qing; Han, Yinglun; Wen, Hongyan; Pang, Yue; Li, Qingwei (Frontiers in Immunology, 2020)
Apolipoprotein genes represent a large family of genes encoding various binding proteins associated with plasma lipid transport. Because of their long divergence history, it needs confirm whether and how these genes have evolved from a common ancestor through gene duplication and original function. Based on the phylogenetic tree, sequence alignment, motifs and evolutionary analysis  of gene synteny and collinearity, apolipoprotein LAL1 and LAL2 in lamprey may be the common ancestor of APOA, APOC, APOE in higher vertebrate, traced back to 360 million years ago. The results of immunofluorescence, immunohistochemistry, flow cytometry and laser confocal microscopy show that LAL2 is mainly distributed in the liver, leukocytes and kidney of lampreys, localized in the cytoplasm of liver cells and leukocytes, even secreted into sera. The results of surface plasmon resonance technology demonstrates that LAL2 colocalizes to MCF-7/K562 cells associated with LIP and further enhances the killing effect of LIP on tumor cells. In addition, lampreys were stimulated with Staphylococcus aureus, Vibrio anguillarum, and Poly I:C at different time, the relative expression of lal2 gene and protein level significantly increase through qPCR and western blot methods. LAL2 can recognize and bind to Gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) and Gram-negative bacteria (Escherichia coli), and play an important role in the antibacterial process. Collectively, our data reveal a long, complex evolutionary history for apolipoprotein genes under different selection pressure, confirm immune effect of LAL2 in lamprey sera against pathogens, and lay the foundation for the further biological function research of lamprey immune system.